Returning Chinese school-aged children and adolescents to physical activity in the wake of COVID-19: Actions and precautions - Chen, P.; Mao, L.; Nassis, G. B.; Harmer, P.; Ainsworth, B. E.; Li, F. (Journal of Sport and Health Science, 2020)
The Coronavirus disease-2019 (COVID-19) pandemic is still spreading globally. As of April 7, 2020, it has reached 184 countries and territories, infecting more than 1.4 million people worldwide with more than 82,000 deaths.1 The situation in China has improved significantly since December 31, 2019.2 Owing to the unprecedented and effective quarantine measures taken across the country, Chinese health authorities reported on March 18, 2020, that for the first time since the outbreak no new locally transmitted COVID-19 cases had been reported, marking a major turning point in the fight against the highly contagious coronavirus.3 Since then, the daily number of new cases in the mainland of China has dropped to double digits, with new infections primarily originating from incoming air passengers from outside China.4